Temporal profiling of M‐TEER‐related complications - Jafer Haschemi; Hanna Schrameck; Jean Marc Haurand; Daniel Oehler; Maximilian Spieker; Fabian Voss; Malte Kelm; Amin Polzin; Patrick Horn (ESC Heart Failure)
Abstract Aims Transcatheter edge‐to‐edge repair of the mitral valve (M‐TEER) is known for its low complication rates. However, the optimal level and duration of post‐procedural care remain unclear. This study aimed to identify the specific timeframe of post‐procedural complications following M‐TEER. Methods and results We conducted a retrospective analysis of 865 patients who underwent M‐TEER at the University Hospital Düsseldorf between August 2010 and August 2023. Our analysis focused on a comprehensive examination of all acute post‐procedural complications (1–100 h), considering the time point of occurrence or diagnosis. The complication analysed included cardiogenic shock, pericardial tamponade, stroke, cardiac arrhythmias, bleeding, acute kidney injury, myocardial infarction, peripheral vascular ischaemia and in‐hospital mortality. Results The median age was 80 (74, 84) years, and the EuroScore II was high (6.5 [4.0, 12.0] %). Functional mitral regurgitation (MR) was more common than degenerative or mixed MR (69% vs. 20%. respectively; 11%). Technical success rate was 97.2%. Overall, acute post‐procedural complications occurred in 87 patients (10.1%). Most complications (75.9%) occurred within the first 4 h post‐procedure. 12.6% of the complications occurred during the period between 4 and 24 h post‐procedure, and 11.5% of the complications happened between 24 and 100 h post‐procedure. Life‐threatening complications were observed only within the first 4 h post‐procedure. Conclusions The majority of post‐procedural complications after M‐TEER occur within the first 4 h, with pericardial tamponade and major bleeding occurring only during this period. These findings provide valuable insight for physicians in determining the optimal surveillance and monitoring duration after M‐TEER within clinical settings.